Simulation of car bumper material using finite element analysis. - Rimy, M.M.; Abdul Aziz, Faieza (Academic Journals Inc., 2010)
Bumper is one of the main parts which are used as protection for passengers from front and rear collision. The aim of this study was to analyze and study the structure and material employed for car bumper in one of the national car manufacturer. In this study, the most important variables like material, structures, shapes and impact conditions are studied for analysis of the bumper beam in order to improve the crashworthiness during collision. The simulation of a bumper is characterized by impact modelling using Abaqus 6.9 according to the speed that is 13.3 m sec-1 (48 km h-1) given in order to analyse the results. This speed is according to regulations of Federal Motor Vehicle Safety Standards, FMVSS 208- Occupant Crash Protection whereby the purpose and scope of this standard specifies requirements to afford impact protection for passengers. In this research, the three types of material were selected that are relevant to be applied to the front bumper beam. The materials consist of Expanded Polypropylene (EPP), Glass Mat Thermoplastics (GMT) and Sheet Molding Compound (SMC). These materials were studied by impact modelling to determine the kinetic energy, potential energy and strain energy. The selected materials are compared to each other to find the best material with highest material strength and structure. Simulation using Finite Element Analysis software, which is ABAQUS was conducted. The results showed that a modified SMC bumper can reduce the impact of collision with higher performance and was suggested to replace GMT and EPP. The duration taken for SMC to deflect the impact was the shortest compared to GMT and EPP The findings also showed that EPP cannot totally absorb the energy and reduce the impact of collision.